Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd007859
|View full text |Cite
|
Sign up to set email alerts
|

Initial arch wires for alignment of crooked teeth with fixed orthodontic braces

Abstract: Analysis 3.4. Comparison 3 0.014 inch superelastic NiTi wire versus 0.015 inch multistrand stainless steel wire, Outcome 4 Pain intensity (VAS (4th day

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Although all patients were bonded with fixed edgewise maxillary appliances, some variation of the initial arch wire may have occurred, and this was not accounted for during the minimization 26 process. However, a systematic review conducted by Wang et al 27 concluded that patient discomfort does not appear to be significantly altered by the type or size of the initial aligning arch wire.…”
Section: Methodsmentioning
confidence: 99%
“…Although all patients were bonded with fixed edgewise maxillary appliances, some variation of the initial arch wire may have occurred, and this was not accounted for during the minimization 26 process. However, a systematic review conducted by Wang et al 27 concluded that patient discomfort does not appear to be significantly altered by the type or size of the initial aligning arch wire.…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18] Bearing these studies in mind, there are no definite conclusions as to which archwire is associated with the least pain. 19 Therefore, the aim of this study was to evaluate the pain experience during the initial aligning phase of orthodontic treatment with three types of NiTi wires: superelastic NiTi, thermoelastic NiTi, and Nitinol aligning archwires. Further aims were to examine any possible associations between age, gender, and degree of crowding/teeth irregularity and the pain intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Bearing these studies in mind, there are no definite conclusions as to which archwire is the best in terms of alignment efficiency. 15 Therefore, the aim of this study is to compare clinically three types of NiTi archwires in terms of the efficiency of alignment each affords.…”
Section: Introductionmentioning
confidence: 99%